The removal of crystal violet from textile wastewater using palm kernel shell-derived biochar - Kyi, Phyo Phyo; Quansah, Jude Ofei; Lee, Chang Gu; Moon, Joon Kwan; Park, Seong Jik (Applied Sciences (Switzerland), 2020)
In this study, we explored the adsorption potential of biochar derived from palm kernel shell (BC-PKS) as an affordable adsorbent for the removal of crystal violet from wastewater. Kinetics, equilibrium, and thermodynamics studies were carried out to evaluate the adsorption of crystal violet onto BC-PKS. The kinetics adsorption process followed the pseudo-second-order model, indicating that the rate of adsorption is principally controlled by chemisorption. The adsorption equilibrium data were better fitted by the Langmuir isotherm model with a determination coecient of 0.954 and a maximum adsorption of 24.45 mg/g. Thermodynamics studies found the adsorption of crystal violet by BC-PKS to be endothermic with increasing randomness at the BC-PKS/crystal violet interface. The percentage removal and adsorption capacity increased with the pH of the solution, as the negative charges on the biochar surface at high pH enhance the electrostatic attraction between crystal violet molecules and BC-PKS. Increasing the BC-PKS dosage from 0.1 to 1.0 g increased percent removal and decreased the adsorption capacity of crystal violet onto BC-PKS. Therefore, biochar from agricultural by-products, i.e., palm kernel shell, can be cost-effective adsorbents for the removal of crystal violet from textile wastewater.
Keywords: Adsorption; Agricultural byproduct; Biochar; Crystal violet; Palm kernel shell